2017
DOI: 10.5993/ajhb.41.3.15
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Implicit Racial Bias in Recognition of Child Abuse

Abstract: We demonstrated an experimental approach to study the influence of implicit racial bias on recognition of child abuse. Though we failed to find an effect, it is too early to conclude that none exists. The relationship among human cognition, behavior, and healthcare disparities is complex. Studies are needed that incorporate diverse approaches, clinical contexts and scenarios, patient and physician characteristics, and validated measures if we are to understand how it might be used to reduce healthcare disparit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…This study found an association between implicit racial bias and markers of poor visit communication and poor ratings of care, especially in Black patients [36]. Three studies found evidence of implicit bias but found no evidence that it affects clinician's provision of care or that it predicts treatment recommendations to minority patients [27,32,34]. Similarly, two studies that measured race and social class implicit bias found that their participants had an implicit preference for White persons and for those in the upper social class [30,31].…”
Section: Race and Social Classmentioning
confidence: 74%
See 4 more Smart Citations
“…This study found an association between implicit racial bias and markers of poor visit communication and poor ratings of care, especially in Black patients [36]. Three studies found evidence of implicit bias but found no evidence that it affects clinician's provision of care or that it predicts treatment recommendations to minority patients [27,32,34]. Similarly, two studies that measured race and social class implicit bias found that their participants had an implicit preference for White persons and for those in the upper social class [30,31].…”
Section: Race and Social Classmentioning
confidence: 74%
“…Majority of the studies reported the presence of moderate to strong implicit bias among the participants. Twelve studies found strong evidence of implicit bias favoring White Americans [25][26][27][28][29][30][31][32][33], while two studies found weak to moderate evidence of race bias [34,35]. Green et al (2007) found implicit stereotypes of African Americans as less cooperative with medical procedures [10].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations